Fostering Pro-Environmental Attitudes in Early Childhood: Project-Based Learning as a Pedagogical Innovation for Greenpreneurship Development - Endang Sungkawati; Ni Wayan Suarniati; Oleh Predmestnikov; Ionut Cristian Scurtu (Jurnal Pendidikan Anak, 2026)
Purpose: This study examines the effectiveness of Project-Based Learning (PjBL) as a pedagogical innovation to nurture greenpreneurship attitudes among kindergarten students, aligning with Education for Sustainable Development (ESD) principles. Methodology: This study employed a quantitative observational approach, involving 39 students at Kuncup Melati Kindergarten, Blitar. Data were gathered through structured observation instruments measuring children’s greenpreneurship attitudes across four dimensions: environmental awareness, eco-friendly creativity, responsibility, and initiative. Analysis was conducted using descriptive statistics and simple linear regression to assess the impact of PjBL implementation on the development of these attitudes. Findings: The results demonstrate a significant positive improvement in children’s greenpreneurship attitudes following the PjBL intervention, with a regression coefficient of 0.404. Environmental awareness and responsibility emerged as the most developed dimensions, while creativity and initiative showed meaningful progress. Statistical analysis confirmed that PjBL significantly influences the development of a sustainable entrepreneurial mindset (p < 0.05). Implications: The findings underscore that PjBL serves as an effective operational framework for integrating ESD into early childhood education, transforming abstract sustainability concepts into concrete, actionable learning experiences. Recommendations: Educators and policymakers should prioritize project-based, sustainability-focused curricula to foster innovative and environmentally conscious future generations. Originality/Value: By expanding the scope of greenpreneurship to the early childhood level, this research provides empirical evidence that sustainability-oriented pedagogical innovations can effectively cultivate proactive character traits and environmental responsibility from an early age.